Adjuvant treatments for resected pancreatic adenocarcinoma: a systematic review and network meta-analysis - Liao, Wei-Chih; Chien, Kuo-Liong; Lin, Yu-Lin; Wu, Ming-Shiang; Lin, Jaw-Town; Wang, Hsiu-Po; Tu, Yu-Kang (The lancet oncology, 2013)
Major adjuvant treatments for pancreatic adenocarcinoma include fluorouracil, gemcitabine, chemoradiation, and chemoradiation plus fluorouracil or gemcitabine. Since the optimum regimen remains inconclusive, we aimed to compare these treatments in terms of overall survival after tumour resection and in terms of grade 3–4 toxic effects with a systematic review and random-effects Bayesian network meta-analysis. We searched PubMed, trial registries, and related reviews and abstracts for randomised controlled trials comparing the above five treatments with each other or observation alone before April 30, 2013. We estimated relative hazard ratios (HRs) for death and relative odds ratios (ORs) for toxic effects among different therapies by combining HRs for death and survival durations and ORs for toxic effects of included trials. We assessed the effects of prognostic factors on survival benefits of adjuvant therapies with meta-regression. Ten eligible articles reporting nine trials were included. Compared with observation, the HRs for death were 0·62 (95% credible interval 0·42–0·88) for fluorouracil, 0·68 (0·44–1·07) for gemcitabine, 0·91 (0·55–1·46) for chemoradiation, 0·54 (0·15–1·80) for chemoradiation plus fluorouracil, and 0·44 (0·10–1·81) for chemoradiation plus gemcitabine. The proportion of patients with positive lymph nodes was inversely associated with the survival benefit of adjuvant treatments. After adjustment for this factor, fluorouracil (HR 0·65, 0·49–0·84) and gemcitabine (0·59, 0·41–0·83) improved survival compared with observation, whereas chemoradiation resulted in worse survival than fluorouracil (1·69, 1·12–2·54) or gemcitabine (1·86, 1·04–3·23). Chemoradiation plus gemcitabine was ranked the most toxic, with significantly higher haematological toxic effects than second-ranked chemoradiation plus fluorouracil (OR 13·33, 1·01–169·36). Chemotherapy with fluorouracil or gemcitabine is the optimum adjuvant treatment for pancreatic adenocarcinoma and reduces mortality after surgery by about a third. Chemoradiation plus chemotherapy is less effective in prolonging survival and is more toxic than chemotherapy. None.